Proposed Marketing Strategy for Increasing Sales in Restaurant Business - Muhamad Fachrian Kesumaputra (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This study aims to formulate an effective marketing strategy to increase sales at Gianni’s Pizza Shop, a New York-style pizza restaurant located in Jakarta. The research employs a mixed-method approach combining qualitative and quantitative data. Key analytical tools include STP (Segmentation, Targeting, and Positioning), Marketing Mix (4P), SWOT, VRIO framework, and Porter’s Five Forces to assess internal and external business environments. Data was gathered through surveys distributed via online platforms and analyzed to understand consumer preferences, brand awareness levels, and competitive positioning. The findings reveal that while Gianni’s has unique strengths—such as a distinctive concept, strategic location, and spacious ambiance—its limited brand recognition and weak online presence hinder sales performance. Survey results show that the 17–28 age group in South Jakarta values affordable pricing, classic pizza flavors, and vibrant dining atmospheres. However, current digital promotions and customer engagement through social media are inadequate. Based on the analysis, the study proposes several strategies: enhancing digital marketing campaigns, collaborating with influencers, improving delivery services through online food platforms, and hosting community events to increase customer interaction and loyalty. The study contributes to practical marketing applications by providing an integrative model for small food and beverage businesses to strengthen brand positioning and customer reach. The implications emphasize the importance of aligning promotional efforts with consumer expectations and leveraging local market trends to achieve sustainable sales growth.